2016
DOI: 10.1371/journal.pone.0159367
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Domestic Violence in Hong Kong Chinese Women Presenting with Urinary Symptoms

Abstract: ObjectivesTo determine the prevalence of domestic violence and its risk factors in women presenting with urinary symptoms.MethodsThe study was carried out in the urogynecology clinic and general gynecology clinic, Department of Obstetrics and Gynecology, Queen Mary Hospital, Hong Kong from 1st May 2013 till 31st October 2014. Two hundred and twenty-five women presenting to the urogynecology clinic with urinary symptoms were categorized according to their symptoms and were asked to complete the Modified Abuse A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Moreover, this clinical feature is the main predictor within the pattern of diagnoses related to a potential violence by partner (orange community). This finding is coherent with the literature on domestic violence from other countries, focusing on the chronic dimension of violence which has a number of stress-related clinical outcomes such as genitourinary disease [32] or psychosomatic [33]. Traumatic event and/or chronic stress of domestic violence may cause also a wide range of psychological conditions from personality disorders (e.g.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Moreover, this clinical feature is the main predictor within the pattern of diagnoses related to a potential violence by partner (orange community). This finding is coherent with the literature on domestic violence from other countries, focusing on the chronic dimension of violence which has a number of stress-related clinical outcomes such as genitourinary disease [32] or psychosomatic [33]. Traumatic event and/or chronic stress of domestic violence may cause also a wide range of psychological conditions from personality disorders (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…Alcohol and substance abuse diagnoses, as expected from previous studies [5, 3235], was found to be another strong predictor of violence. In fact, alcohol use in both victims and aggressors was found to be associated with more severe violence.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Studies in Hong Kong showed that the prevalence of domestic violence directed against women ranged from 10.4 to 15.7% [ 1 , 2 ]. These figures are lower than the global prevalence of around 25% [ 3 ], including that in the U.S. [ 4 ] Domestic violence, also known as intimate partner violence, refers to any behavior within an intimate relationship that causes physical, emotional and sexual harm to the spouse/partner [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…As most women are reluctant to actively disclose experiences of being abused due to fears and concerns about the consequences of disclosure (Ma & Pun, 2016), universal or targeted screening for DV among female patients has been promoted in some countries such as the United States and Israel (Daoud et al, 2019). Patients might be screened (with the use of a questionnaire) or asked by doctors and/or nurses for DV issues (O'Doherty et al, 2015).…”
Section: Introductionmentioning
confidence: 99%